FRI0378 Chondrocalcinosis – a fresh look at established and novel risk factors. (23rd January 2014) - Abhishek, A.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Background: Chondrocalcinosis (CC), predominantly a result of calcium pyrophosphate crystal deposition (CPPD) occurs due to a combination of excess synovial fluid extracellular pyrophosphate (PPi) and favourable cartilage matrix changes. The association between CC and several conditions which suggest the presence of high PPi levels or excess nucleating factors has not been examined before. Objectives: To ascertain the association between CC and (1) demographic factors like age, sex, body mass index (BMI); (2) conditions associated with high PPi levels - single nucleotide polymorphisms (SNPs) in genes involved in PPi metabolism, low bone mineral density (BMD) and excess joint loading; (3) exposures suggesting an increase in nucleating factors – either generalised (e.g. vascular or soft-tissue calcification) or joint specific factors (e.g. knee arthroscopy and/or meniscectomy, knee injury). Methods: A case-control study embedded in GOAL – the Genetics of Osteoarthritis and Lifestyle study (n=3, 170). All participants filled in a detailed questionnaire self-reporting current and early adult life exposures. They were examined by a trained research nurse, and had radiographs of knees, hands, and pelvis. Calcaneal DEXA was measured and genomic DNA was extracted from peripheral blood. Radiographs were scored for OA, CC, vascular calcifications (pelvic radiographs), peri-articular calcification (knee radiographs), and for metacarpal index (measure of cortical BMD). Cases had CC at any joint, and controls did not have CC at all joints. SNPs in the ankylosis human, tissue non-specific alkaline phosphatase, ectonucleotide pyrophosphatase 1, high ferritin, and transferrin gene were selected for examining association with CC. Odds ratio (OR), 95% confidence interval (CI) were used to measure associations between risk factors and CC and adjusted for age, gender, BMI, and knee or hip OA (Kellgren and Lawrence score ≥2 at any hip or ≥3 at any knee). For this analysis, age, BMI, and BMD were converted to tertiles. Results: Age but not sex associated with CC (Table 1 ). There was a negative association between BMI, cortical BMD and CC. Peri-articular and vascular calcification associated with CC. However, there was no association between diuretic intake and CC, and no evidence of association between the 17 candidate SNPs in genes involved in PPi metabolism and CC. Self-reported arthroscopy and/or meniscectomy, knee injury, and occupational joint loading all associated with CC at the same knee (aORs ranging from 2.62 (1.45-4.72) to 1.59 (1.04-2.05)). Conclusions: We have identified several novel risk factors for CC, including low cortical BMD and low BMI. The association between vascular and soft-tissue calcification and CC suggests a generalised "pro-nucleation" state. The absence of an association between SNPs and CC may be due to the fact that the genetic effects are small, and that this study is not powered enough to detect these differences. Disclosure of Interest: None Declared